Optimale leerschema’s bij dementie - Diesfeldt, Han F.A. (Tijdschrift voor Gerontologie en Geriatrie, 2015)
Bespreking: Materne, C. J., Luszcz, M.A. & Bond, M.J. (2014). Onceweekly spaced retrieval training is effective in supporting everyday memory activities in community dwelling older people with dementia. Clinical Gerontologist, 37:475–492. Creighton, A.S., Davison, T.E., Van der Ploeg, E.S., Camp, C. J. & O’Connor, D.W. (2015). Using spaced retrieval training to teach people with dementia to independently use their walking aids: two case studies. Clinical Gerontologist, 38:170–178.